Tear trough deformity: different types of anatomy and treatment options - Jiang, Jindou; Wang, Xuekun; Chen, Rongrong; Xia, Xueying; Sun, Sai; Hu, Kuikui (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Aim : To explore the efficacy of tear trough deformity treatment with the use of hyaluronic acid gel or autologous fat for soft tissue augmentation and fat repositioning via arcus marginalis release. Material and methods : Seventy-eight patients with the tear trough were divided into three groups. Class I has tear trough without bulging orbital fat or excess of the lower eyelid skin. Class II is associated with mild to moderate orbital fat bulging, without excess of the lower eyelid skin. Class III is associated with severe orbital fat bulging and excess of the lower eyelid skin. Class I or II was treated using hyaluronic acid gel or autologous fat injections. Class III was treated with fat repositioning via arcus marginalis release. The patients with a deep nasojugal groove of class III were treated with injecting autologous fat into the tear trough during fat repositioning lower blepharoplasty as a way of supplementing the volume added by the repositioned fat. Results : Seventy-eight patients with tear trough deformity were confirmed from photographs taken before and after surgery. There were some complications, but all had complete resolution. Conclusions : Patients with mild to moderate peri-orbital volume loss without severe orbital fat bulging may be good candidates for hyaluronic acid filler or fat grafting alone. However, patients with more pronounced deformities, severe orbital fat bulging and excess of the lower eyelid skin are often better served by fat repositioning via arcus marginalis release and fat grafting.